Number of Hours of Sleep with Changes in Blood Pressure Amongst Medical Students in Western Maharashtra - Tarwani, Dimple Manoj; R, Kunkulol R; Chaudhari, Sohan; Batwal, Chinmaye; Thaliath, Liz (International Journal of Clinical and Biomedical Research, 2019)
Introduction: Sleep has become one of the most ignored factors today. More sleep or less sleep does not matter it is just compensated the next day. Importance of regular and timely sleep amongst the students and their correlation with blood pressure is necessary to be found out so that the students can be made aware of and can be provided treatment to prevent further complications. Method: Demographic profile was noted it includes name, age, gender, professional year of MBBS and residence. History of sleeping was noted and other factors which influences sleeping pattern (i.e, alcohol, smoking, an association of dreams with sleep, midnight awakenings with sleep, caffeine intake before bed and average stress levels) through a well-structured questionnaire. Blood pressures of all eligible students were recorded 3 times in a week at the same time by the principal investigator with the same instrument according to the JNC 7 classification for hypertension. Results: Amongst all the medical students, 6% had systolic hypertension and 22.50% had diastolic hypertension. Comparing blood pressures according to sleeping patterns, amongst cases (less than 5 hours of sleep) 20.8% had systolic hypertension and 56.30% had diastolic hypertension. Whereas in controls (more than 5 hours of sleep) 1.40% had systolic hypertension and 11.90% had diastolic hypertension. Factors such as alcohol consumption, smoking, caffeine consumption before sleep, dreams, midnight awakenings and stress were found to be associated with sleeping patterns and the results were found to be extremely significant (p<0.0001) statistically. Conclusion: Sleep duration of less than 5 hours was noted in 24% of the total population. The subjects with lesser number of sleeping hours had increased levels of blood pressure and a higher prevalence of hypertension. The average systolic blood pressure in subjects with less than 5 hours of sleep (cases) showed 48.50% pre-hypertensives and 20.80% hypertensives whereas in case of average diastolic blood pressure 18.50% were prehypertensive and 56.30% were hypertensive. Keywords: Blood pressures; Sleeping hours; Medical Students.